Psychological and Pedagogical Aspects of Formation of Interpersonal Relations Among Cadets (Eurasian Scientific Herald, 2023)
This article applies the results of a scientific study of the manifestation of military-value relations by establishing cooperation, such as getting along with each other, transferring various information to each other, exchanging ideas, etc.